Spreadsheet-Based Automatic Print Cost Calculator - Mokhamad Ariel Fadilah; Izza Anshory; Jamaaluddin Jamaaluddin; Agus Hayatal Falah (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
Production cost calculation is a crucial factor that impacts productivity and profitability in the printing industry. This study presents an automatic print costing tool that runs on a spreadsheet and is intended to increase operational efficiency and calculation accuracy in Small and Medium-Sized Printing Enterprises (SMEs). With the use of Esp32 as a microcontroller, TCS3200 and infrared sensors, this project seeks to create an automated print pricing spreadsheet that would help printing SMEs swiftly and precisely determine product prices. This tool's components include an LCD to show the cost computation findings, an infrared sensor to identify the number of printed sheets, a TCS3200 sensor to determine whether or not colored paper is present, and a push button feature to resume the calculation and upload the entire cost to the spreadsheet. The instrument functions effectively and aids users in doing cost calculations in an efficient manner, according to the findings. Despite some challenges, such as slow internet connections that cause delays, to enable effective cost assessment poor internet connection. This strategy should decrease calculation errors and increase manufacturing cost management effectiveness.